Digestible protein levels and metabolic responses in juvenile piapara (Megaleporinus obtusidens) - De Almeida, Viviane Do Nascimento Santana [UNESP]; Carli, Gabriela Castellani [UNESP]; Sátiro, Thaise Mota [UNESP]; Do Nascimento, Thiago Matias Torres [UNESP]; Takahashi, Leonardo Susumu [UNESP] (Boletim do Instituto de Pesca, 2023)
This study aimed to determine the effects of dietary digestible protein (DP) on growth and physiological indicators in piapara. Three hundred piapara juveniles (24.0 ± 1.3 g) were distributed in 20 tanks of 130 L (15 fish/tank) with continuous aeration and water. Five isoenergetic diets (14.0 MJ·kg-1) were formulated to contain increasing levels of DP (21, 24, 27, 30 and 33%). After 77 days of feeding, increasing levels of digestible protein influenced final weight, specific growth rate and weight gain linearly (p < 0.05). Water ammonia concentration and liver alanine aminotransferase activity also showed a linear effect with an increasing DP level (p < 0.05), but no relationship was found between DP level and serum ammonia (p > 0.05). There was no linear and quadratic effect for hepatosomatic index, liver glycogen and liver lipid content (p > 0.05). On the other hand, the muscle lipid content decreased linearly with the increase in the DP level (p < 0.05), while the mesenteric fat index showed a linear and quadratic effect (p < 0.05) with an increasing curve until the peak of 25.77% DP. The activity of the hepatic malic enzyme also followed a quadratic pattern (p < 0.05) with a maximum point of 27.08% of DP. This contrasts with the hepatic enzyme glucose- 6-phosphate dehydrogenase, which increased linearly with the increase in the DP level (p < 0.05). The results showed better productive performance for fish fed with the highest levels of DP, though greater excretion of ammonia in the water was also shown. Diets below 27% DP resulted in greater energy reserve, amino acid catabolism and lipogenesis. Therefore, the inclusion of 28 to 30% DP in the diet will be ideal for growth and physiological responses in piapara.
Níveis de proteínas digestíveis e respostas metabólicas em juvenis de piapara (Megaleporinus obtusidens)
Keywords: Energy retention; Omnivorous; Performance; Physiological indicators